1992
DOI: 10.1111/j.1432-1033.1992.tb17190.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid vesicles which can bind to protein kinase C and activate the enzyme in the presence of EGTA

Abstract: Maximal protein kinase C activity with vesicles of phosphatidic acid and 1,2-di0leoyl-~sn-glycerol is observed in the absence of added Ca2 '. Addition of phosphatidylcholine to these vesicles restores some calcium dependence of enzyme activity. 1,2-Dioleoyl-sn-glycerol eliminates the Ca2 +-dependence of protein kinase C activity found with phosphatidic acid alone. Phorbol esters do not mimic the action of 1,2-dioleoyl-sn-glyceroI in this respect. This suggests that the 1,2-dioleoyl-sn-glycerol effect is a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Similarly, because Ca 2ϩ and PS act allosterically (24), considerably less Ca 2ϩ is required to achieve the same level of binding to PMA-containing membranes compared with DG-containing membranes. Indeed, the affinity for PS, in the presence of DG, is sufficiently high that significant association occurs in the absence of Ca 2ϩ (24,36). Thus, the chelator resistance reflects the extraordinarily high affinity interaction with PMA-containing membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, because Ca 2ϩ and PS act allosterically (24), considerably less Ca 2ϩ is required to achieve the same level of binding to PMA-containing membranes compared with DG-containing membranes. Indeed, the affinity for PS, in the presence of DG, is sufficiently high that significant association occurs in the absence of Ca 2ϩ (24,36). Thus, the chelator resistance reflects the extraordinarily high affinity interaction with PMA-containing membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several groups have described PA-responsive protein kinases that to date remain unidentified but that have been determined as separate from known members of the PKC superfamily [125][126][127]. Early in vitro studies investigating lipid regulation of the classical PKC isoenzymes demonstrated an ability of PA to substitute for PS in the activation of PKC [28,123,124]. Importantly, the potency and specificity of PA substitution for PS were dependent upon whether the assay was performed with Triton X-100 mixed micelles or with sonicated lipid vesicles containing lipid bilayers [28,128].…”
Section: Regulation Of Pkc Through Pamentioning
confidence: 99%
“…2). Although the physiological function of PA per se is not well understood, several in vitro and in vivo targets of PA have been identified, including PIP 5-kinase [119], PI-PLCb [120], Raf-1 [121], protein phosphatase 1 [122] and PKC itself [28,123,124]. In addition, several groups have described PA-responsive protein kinases that to date remain unidentified but that have been determined as separate from known members of the PKC superfamily [125][126][127].…”
Section: Regulation Of Pkc Through Pamentioning
confidence: 99%
“…Although the lack of conviction about DAG signaling in plants is not an argument for the importance of PtdOH, its acceptance as a signal in animal cells, together with our demonstration of its biological activity in C. eugametos, means that it should now receive more attention from plant cell biologists. In animal cells, no consensus picture has yet formed about how PtdOH operates, but a number of recent reports describe a nove1 type of protein kinase that is specifically activated by this lipid ( Figure 1OB; Bocckino et al, 1991;Epand et al, 1992;Nakanishi and Exton, 1992;Stasek et al, 1993;Khan et al, 1994;Limatola et al, 1994). Another potentia1 site of action appears to be the PLC signaling cascade itself, because PtdOH has been found to activate PtdlnsP 5-kinase and PLC specifically (Jackowski and Rock, 1989;Kroll et al, 1989;Moritz et al, 1989;Hashizume et al, 1992;Jacob et al, 1993;Jones and Carpenter, 1993), in this way amplifying the PLC signaling cascade ( Figure 1OB).…”
Section: Activation Of Plc and Pldmentioning
confidence: 99%